An initial screening of commercial phosphorus ligands on the recovery of metal ions from red mud. (2021) - Narayanan, Remya P.; Palantavida, Shajesh
Abstract: The manufacturing of alumina from bauxite through the Bayer process generates a large amount of highly alkaline waste called bauxite residue or "Red mud". The annual generation of bauxite residue throughout the world is around 120 million tons and 2.7 billion tons of it has already been stockpiled. Methods for large scale remediation of red mud are an active area of interest around the world. One of the prime challenges to overcome is to ensure that the remediation process is economically feasible. Red mud is a potential source for various metal oxides (oxides of Al, Fe, Ti, Si, Ca, Na and Mg) and many valuable metal ions (including rare earth and transition metals). Out of the mixture of metal ions rare earth (RE) elements are the most economically and strategically important component. The remediation process can be made economical if the rare earth portion of the mixture can be effectively separated into a product. An economically viable process was developed by the authors for the recovery of scandium as Sc2 O3 from Jamaican red mud. Even though the developed process was profitable, since the amount of scandium is too low in the red mud the process couldn't resolve the remediation in terms of large volume waste management. Herein we are reporting an initial study conducted to develop a solvent extraction method for the selective recovery of the large volume elements as well as the critically important rare earth elements by using commercially available phosphorus ligands from simulated waste liquor.